Rethinking dance history issues and methodologies - Morris, Geraldine; Nicholas, Larraine (London New York Routledge, Taylor & Francis Group, 2018)
The need to rethink and question the nature of dance history has not diminished since the first edition of Rethinking Dance History (2004). The revised second edition addresses the needs of an ever-evolving field, with new contributors including , for example: new archival practices; the subtleties of gender and ethnic inclusivity in creating historical narratives; and the increasing importance of performing dances from the past as a route to historical knowledge. A two-part structure divides the book's contributions into: Why dance history? - the ideas, issues and key conversations that underpin the study of dance history; Researching and writing - discussions of the methodologies and approaches behind successful research in this area. Everyone involved with dance creates and carries with them a history, and this volume explores the ways in which these histories inform a sense of the past - from memories which establish identity to re-invention or preservation through shared and personal heritages. Considering the potential significance of studying dance history for scholars, philosophers, choreographers, dancers and students alike, Rethinking Dance History is an essential starting point for anyone intrigued by the rich history of dance
Part 1. Introduction: Why dance history? -- Part 2. Introduction: Researching and writing
Revised edition of: Rethinking dance history : a reader / edited by Alexandra Carter. 2004
Includes bibliographical references and index
Keywords: Dance -- History